Design of dense fiber-wireless system with load consideration - Dipa, Mahfida Amjad; Yaakob, Syamsuri; Fadlee, Mohd; Ahmad, Faisul Arif (2025)
This paper presents data transmission capability over 5G new radio FR1 and FR2 bands. The co-transmission of 4GHz and 30GHz radio frequency signals is considered to represent macro and microcells, respectively, in the system. The article considers wireless coverage in the dense cellular deployment scenario with high user densities for Radio-over-Fiber technology. The proposed system consists of one fiber-based link for 10km at the transmitter end and a wireless range up to 10m 10m, utilizing the optical wireless channel component at the receiver end. According to the simulated results, the fiber-wireless system is capable of transmitting the radio frequency signals, achieving a minimum BER of 10-9 and 6m wireless coverage for both cells. Additionally, it also depicts that the system is balanced when the user load is 20, maintaining the maximum achievable average cell throughput of 110.49 Mbps, and a spectral efficiency of 6.52 bits/s/Hz for macro and microcells in the fiber-wireless system.